A medical student’s experience of Nepal earthquake, 2015 (Journal of Patan Academy of Health Sciences, 2020)
A magnitude 7.8 earthquake struck Nepal on April 25, 2015 killing nearly 9,000 people and injured nearly 22,000.  The tremor at 11:56 am shook Nepal destroying lives and infrastructures, and most importantly dreams and hopes of people. I, as a medical student, express my experiences and joy of helping person in need during these devastating days.